IL-6 blockade in systemic juvenile idiopathic arthritis - achievement of inactive disease and remission (data from the German AID-registry) - M. Bielak; E. Husmann; N. Weyandt; J.-P. Haas; B. Hügle; G. Horneff; U. Neudorf; T. Lutz; E. Lilienthal; T. Kallinich; K. Tenbrock; R. Berendes; et al. (BMC, 2018)
Abstract Background Systemic juvenile idiopathic arthritis (sJIA) is a complex disease with an autoinflammatory component of unknown etiology related to the innate immune system. A major role in the pathogenesis has been ascribed to proinflammatory cytokines like interleukin-6 (IL-6), and effective drugs inhibiting their signaling are being developed. This study evaluates sJIA patients treated with the IL-6 inhibitor tocilizumab (TCZ) concerning clinical response rate, disease course and adverse effects in a real-life clinical setting. Methods In 2009 a clinical and research consortium was established, including an online registry for autoinflammatory diseases (AID) (https://aid-register.de). Data for this retrospective TCZ study were documented by 13 centers. Results From 7/2009 to 4/2014, 200 patients with sJIA were recorded in the AID-registry. Out of these, 46 (19 m, 27 f, age 1-18 years) received therapy with TCZ. Long term treatment (median 23 months) has been documented in 24/46 patients who were evaluated according to Wallace criteria (active disease 6/24, inactive disease 5/24, remission 13/24 cases). Under observation co-medication were used in 40/46 cases. Adverse events were reported in 11/46 patients. The clinical response rate (no clinical manifestation, no increased inflammation parameters) within the first 12 weeks of treatment was calculated to be 35%. Conclusion Out of 200 sJIA children reported in the German AID-registry, 46 were treated with TCZ, showing a clinical response rate of 35% during the first 12 weeks, and inactive disease and/or remission under medication in 75% after one year. Adverse events were seen in 24% and severe adverse events in 4%. Trial registration The AID-Registry is funded by the BMBF (01GM08104, 01GM1112D, 01GM1512D).